Microanalysis of Organic Pigments in Ancient Textiles by Surface-Enhanced Raman Scattering on Agar Gel Matrices - Marilena Ricci; Cristiana Lofrumento; Emilio Castellucci; Maurizio Becucci (Journal of Spectroscopy)
We review some new methods based on surface-enhanced Raman scattering (SERS) for the nondestructive/minimally invasive identification of organic colorants in objects whose value or function precludes sampling, such as historic and archeological textiles, paintings, and drawing. We discuss in detail the methodology we developed for the selective extraction and identification of anthraquinones and indigoids in the typical concentration used in textiles by means of an ecocompatible homogeneous nanostructured agar matrix. The extraction system was modulated according to the chemical properties of the target analyte by choosing appropriate reagents for the extraction and optimizing the extraction time. The system has been found to be extremely stable, easy to use and produce, easy to store, and at the same time able to be analyzed even after long time intervals, maintaining its enhancement properties unaltered, without the detriment of the extracted compound. Highly structured SERS band intensities have been obtained from the extracted dyes adopting laser light excitations at 514.5 and 785 nm of a micro-Raman setup. This analytical method has been found to be extremely safe for the analyzed substrates, thus being a promising procedure for the selective analysis and detection of molecules at low concentration in the field of artworks conservation.